Cooperation of the NEIL3 and Fanconi anemia/BRCA pathways in interstrand crosslink repair. Issue 6 (25th January 2020) - Li, Niu; Wang, Jian; Wallace, Susan S; Chen, Jing; Zhou, Jia; D'Andrea, Alan D
Abstract: The NEIL3 DNA glycosylase is a base excision repair enzyme that excises bulky base lesions from DNA. Although NEIL3 has been shown to unhook interstrand crosslinks (ICL) in Xenopus extracts, how NEIL3 participants in ICL repair in human cells and its corporation with the canonical Fanconi anemia (FA)/BRCA pathway remain unclear. Here we show that the NEIL3 and the FA/BRCA pathways are non-epistatic in psoralen-ICL repair. The NEIL3 pathway is the major pathway for repairing psoralen-ICL, and the FA/BRCA pathway is only activated when NEIL3 is not present. Mechanistically, NEIL3 is recruited to psoralen-ICL in a rapid, PARP-dependent manner. Importantly, the NEIL3 pathway repairs psoralen-ICLs without generating double-strand breaks (DSBs), unlike the FA/BRCA pathway. In addition, we found that the RUVBL1/2 complex physically interact with NEIL3 and function within the NEIL3 pathway in psoralen-ICL repair. Moreover, TRAIP is important for the recruitment of NEIL3 but not FANCD2, and knockdown of TRAIP promotes FA/BRCA pathway activation. Interestingly, TRAIP is non-epistatic with both NEIL3 and FA pathways in psoralen-ICL repair, suggesting that TRAIP may function upstream of the two pathways. Taken together, the NEIL3 pathway is the major pathway to repair psoralen-ICL through a unique DSB-free mechanism in human cells.